MINIMIZING STUNTING PREVALENCE RATES TO CREATE HEALTHY PROVINCES - Paul Sirait; Sondang Sidabutar2 (Health Notions, 2023)
Background: The multiple roles of midwives in the health care system raises a question mark on how sharp this role is in preventing stunting to create a healthy province. This research has an impact on evaluating stunting prevalence reduction programs in healthy provincial programs so that governance improvements can be obtained.Objectives: to obtain certainty status specifically the role of midwives in reducing stunting prevalence in the program to create a healthy province.Methods: This study used a quantitative method with a descriptive design. The research population was midwives and midwifery students (n=59). The inclusion criteria were midwives and midwifery students who took part in healthy provincial seminars. The exclusion criteria were midwives and midwifery students who did not attend the seminar. The control variable was a minimizing stunting prevalence rates in the midwifery perspective. The instrument was a questionnaire that includes demographic data and technical data about the program and the role of midwives. Processing the data was univariate and analyzed descriptively.Results: Of the 59 study populations, 50.9% said the stunting program was urgent, 56.1% was in line with the capacity of the local government, and 50% said the role of midwives had not been maximized, especially in the field of health education (71.9%). The cause of the slow achievement of the program is the lack of cross-sectoral cooperation (61.4%), and the low socioeconomic level of the community (57.9%).Conclusion: This study recommended involving midwives and midwifery students in the formation of a stunting management team, and obtaining accurate data in the prevalence reduction program